Zircon geochronology and geochemistry of syenites in the Yamato Mountains, East Antarctica - Horie, Kenji; Takehara, Mami; Hokada, Tomokazu (2022)
The 13th Symposium on Polar Science/Ordinary sessions [OG] Polar geosciences, Wed. 16 Nov. conference object